2013
DOI: 10.1093/jmicro/dft045
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of cesium at the interlayer region in phlogopite mica

Abstract: To investigate the sorption mechanism of cesium (Cs) into clay minerals, high-resolution (scanning) transmission electron microscopy (TEM/STEM) imaging of Cs in mica (phlogopite) has been conducted. Platy phlogopite powders were immersed in a cesium chloride (CsCl) solution to achieve Cs(+)-K(+) ion-exchange at the interlayer regions in phlogopite. To observe many phlogopite particles with the incident electron beam parallel to the mica layers, cross-sectional thin specimens were prepared from sedimented parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 18 publications
3
47
0
Order By: Relevance
“…7c). The brightest contrast (Cs) is definitely that corresponding to the Cs-occupied interlayer, where each Cs column can be resolved with a separation of 4.5 Å ( Okumura et al, 2014). The medium contrast (K) corresponds to the K-occupied interlayer, or that in biotite, where spots corresponding to the K-columns can be faintly identified.…”
Section: Chemical Compositions and Xrd Patterns Of The Original Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…7c). The brightest contrast (Cs) is definitely that corresponding to the Cs-occupied interlayer, where each Cs column can be resolved with a separation of 4.5 Å ( Okumura et al, 2014). The medium contrast (K) corresponds to the K-occupied interlayer, or that in biotite, where spots corresponding to the K-columns can be faintly identified.…”
Section: Chemical Compositions and Xrd Patterns Of The Original Samplesmentioning
confidence: 99%
“…Several studies have reported that FES plays an important role in Cs sorption and retention (Sawhney, 1972;Zachara et al, 2002;McKinley et al, 2004). On the other hand, recent studies Okumura et al, 2014) have indicated that Cs penetrates deeply inside the crystals, along the interlayer regions by ion-exchange. In these studies, a high-resolu-tion transmission electron microscope (HRTEM) or a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) was used to visualize Cs-replaced interlayer regions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have hypothesized that basal and slow sites have essentially the same NaACs exchange selectivity [4], whereas atomistic simulations suggest that Cs is much more selectively retained in anhydrous clay interlayers than on external basal surfaces [79]. The few geochemical modeling studies that described slow sites as distinct surface sites treated them as ideal cation exchangers [22,100] despite evidence that these sites, at least in some cases, form interstratified structures in which Cs displaces K in some interlayers but not in others [69]. Finally, the adsorption-desorption kinetics of the slow and high-affinity sites remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that FES, which formed around the edges of plate-like mica crystals during weathering, strongly and selectively sorb Cs. 7−9 Recently, however, Kogure et al 10 and Okumura et al 11 used high-resolution transmission electron microscopy (HRTEM) to directly observe Cs ions sorbed deeply in the interlayer region of vermiculite and phlogopite.…”
Section: ■ Introductionmentioning
confidence: 99%